DIALEKTIKA TRADISI MODERNITAS: REKONTRUKSI PENDIDIKAN ISLAM PRESPEKTIF HASYIM ASY'ARI, AHMAD DAHLAN, ZARKASYI - Sal Sabilla Ulayya Zahro; Muhammad Nur Ilhammin; Agis Ayuningtias; M. Yunus Abu Bakar (JIP: Jurnal Ilmu Pendidikan, 2025)
This study analyzes the conceptual restructuring of the Islamic pedagogical systeam through an examination of the intellectual confrontation between conventional traditionalism and contemporary innovation in the thinking of three central figures in Indonesian Islamic education: KH. M. Hasyim Asy'ari, KH. Ahmad Dahlan, and Imam Zarkasyi. All three represent different but complementary epistemological currents in formulating a philosophical reconstruction of Islamic Education. M. Hasyim Asy'ari emphasizes the principles Ahlussunnah Wal Jama'ah as the main foundations of education. Ahmad Dahlan offered the modernization of Islamic education through the integration of religious and general knowledge, rationality, and a practical approach based on the Qur'an. Meanwhile, Imam Zarkasyi combined the strengths of tradition and modernity through the modern Gontor pesantren system, which developed an integrated curriculum, discipline, master of international languages, and professional education management. The result of the study show that the dialectic of thr three thinkers produced a progressive and adaptive reconstruction they built became an important foundation for thr development of Islamic education that is relevant to the challenges of globalization and contemporary social change.